Requirement of handover modeling in the downlink 3GPP long term evolution system - Lin, Cheng-Chung; Sandrasegaran, Kumbesan; Mohd. Ramli, Huda Adibah; Xue, Minjie (IEEE, 2010)
Long Term Evolution (LTE) is the next generation wireless system that uses Break-before-Connect technology in the handover scheme, unlike handover in the Wide-band Code Division Multiple Access (WCDMA) that uses Connect-before- Break technology. In the LTE system, handover is one of the important radio resource management schemes that are responsible for mobility of user equipments, load balancing and interference management. This paper provides detailed description on requirements involved for handover procedure in the LTE system and the feasibility to extend the current software simulation tool of the LTE system to support multiple cells for handover. This paper contributes to the identification of the requirements and specifications that are needed for further study of handover procedure in the LTE system